Strategic control and the possibility of its implementation in private universities A case study of the Arab Academy for Science, Technology and Maritime Transport - احمد, نيرمين; اسبر, لمى (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research sought to assess the possibility of implementing strategic control in private universities, specifically in the Arab Academy for Science, Technology and Maritime Transport in Lattakia, (AASTMT), through (strategic criteria- strategic performance measurement- strategic performance evaluation- corrective actions). The researcher relied on the comprehensive inventory method for the study community, by distributing (62) questionnaires to the scientific and administrative employees at the studied university, which were fully retrieved and analyzed. The researcher used T Student test for one sample as a basic test for this study to analyze the collected data and reach the goal of the study in evaluating the possibility of implementing strategic control. The research found a low level of both strategic standards and corrective actions on the one hand, and a high level of both measuring and evaluating strategic performance on the other hand. The research also concluded a set of recommendations related to the need for clarity and development of strategic standards, and the adoption of an effective incentive system is provided with suitable information in time to discover and correct deviations.